Detection of highly and minimally leukotoxic Actinobacillus actinomycetemcomitans strains in patients with periodontal disease - Cortelli, Sheila Cavalca; Jorge, Antonio Olavo Cardoso [UNESP]; Cortelli, José Roberto; Jordan, Shawn Francis; Haraszthy, Violet Ibyola (Sociedade Brasileira de Pesquisa Odontológica e Faculdade de Odontologia da Universidade de São Paulo, 2003)
This study examined the prevalence of highly and minimally leukotoxic Actinobacillus actinomycetemcomitans in patients with periodontal disease. Pooled subgingival plaque samples from 136 patients with some form of periodontal disease were examined. Subjects were between 14 and 76 years of age. Clinical examinations included periodontal pocket depth (PD), plaque index (PI) and bleeding index (BI). The obtained plaque samples were examined for the presence of highly or minimally leukotoxic A. actinomycetemcomitans strains by the polymerase chain reaction (PCR). Chi-square and logistic regression were performed to evaluate the results. Forty-seven subjects were diagnosed with gingivitis, 70 with chronic periodontitis and 19 with aggressive periodontitis. According to chi-square there was no significant correlation detected between PD (chi2 = 0.73), PI (chi2 = 0.35), BI (chi2 = 0.09) and the presence of the highly leukotoxic A. actinomycetemcomitans. The highly leukotoxic A. actinomycetemcomitans strains were correlated with subjects that were 28 years of age and younger (chi2 = 7.41). There was a significant correlation between highly leukotoxic A. actinomycetemcomitans and aggressive periodontitis (chi2 = 22.06). This study of a Brazilian cohort confirms the strong association between highly leukotoxic A. actinomycetemcomitans strains and the presence of aggressive periodontitis.

O presente estudo avaliou a prevalência de Actinobacillus actinomycetemcomitans de máxima e mínima leucotoxicidade em indivíduos com doença periodontal. Foram analisadas amostras de placa bacteriana subgengival de 136 indivíduos, entre 14 e 76 anos de idade, com algum tipo de doença periodontal. Os parâmetros clínicos avaliados incluíram profundidade de sondagem (PS), índice de placa bacteriana (IPB) e índice de sangramento gengival (ISG). A presença de amostras de A. actinomycetemcomitans de máxima e mínima leucotoxicidade foi avaliada por reação em cadeia da polimerase (PCR). Os resultados foram analisados empregando-se teste qui-quadrado e análise de regressão logística. Quarenta e sete indivíduos apresentaram gengivite, 70 indivíduos periodontite crônica e 19 indivíduos periodontite agressiva. O teste qui-quadrado não demonstrou correlação significativa entre PS (chi2 = 0,73), IPB (chi2 = 0,35), ISG (chi2 = 0,09) e a presença de amostras de máxima leucotoxicidade. A. actinomycetemcomitans de máxima leucotoxicidade apresentou associação com indivíduos com idade inferior a 28 anos (chi2 = 22,06). Os resultados observados nessa população brasileira confirmam a forte associação existente entre amostras de A. actinomycetemcomitans de máxima leucotoxicidade e periodontite agressiva.
Detecção de cepas de Actinobacillus actinomycetemcomitans de máxima e mínima leucotoxicidade em pacientes com doença periodontal
Keywords: Actinobacillus actinomycetemcomitans; Leukotoxin; Gingivitis; Periodontitis; Polymerase chain reaction; Actinobacillus actinomycetemcomitans; Leucotoxina; Gengivite; Periodontite; Reação em cadeia da polimerase